Effects of low-frequency rTMS combined with antidepressants on depression in patients with post-stroke depression: a systematic review and meta-analysis - Pan, Juanhong; Li, Hongpeng; Wang, Yongshen; Lu, Li; Wang, Ying; Zhao, Tianyu; Zhang, Di; Jin, Song (Frontiers in Neurology, 2023)
Abstract Objective: Investigate the effect of low frequency (≤1HZ) repetitive transcranial magnetic stimulation (rTMS) combined with antidepressants on depression and the levels of inflammatory factors IL-6 and TNF-α in patients with post-stroke depression (PSD). Methods: We searched PubMed, Embase, Web of Science, Cochrane Library(CBM), China National Knowledge Infrastructure ( CNKI), Technology Periodical Database (VIP), and Wanfang Database. The search time was from the establishment of the database to October 10, 2022. StataMP 17 and Review Manager 5.3 were used for data analysis. Subgroup analysis was performed for the results with significant heterogeneity (I2≥50% or p < 0.05). StataMP 17 was used to conduct sensitivity analysis to determine the stability of the meta-analysis results further. We used Egger's test to analyze publication bias. Results: A total of 15 RCTs involving 1393 patients with PSD were included. According to the PEDro quality assessment, two studies received high quality (8 scores) and 13 RCTs received moderate quality (6 scores). The meta-analysis showed that low-frequency rTMS combined with an antidepressant significantly reduced HAMD score and NIHSS score, reduced IL-6 and TNF-α levels, and improved MMSE score in patients with PSD compared with an antidepressant alone. Conclusion: The results of this Meta-analysis showed that low-frequency rTMS combined with an antidepressant was more effective than an antidepressant alone in the treatment of PSD. Low-frequency rTMS combined with therapy can not only improve the depression state of patients but also reduce the serum levels of inflammatory factors IL-6 and TNF-α/and improve the cognitive function of patients with PSD. In addition, low-frequency rTMS was associated with fewer adverse effects, proving the safety of rTMS combination therapy. However, there are shortcomings, such as a lack of long-term follow-up, different intervention sites of low-frequency rTMS, and different intervention frequencies (0.5HZ or 1HZ). In the future, more RCTs with large sample sizes, higher quality, and more extended observations to verify further the effectiveness of low-frequency rTMS combined therapy on PSD. A new meta-analysis should determine which intervention sites and frequency are more effective in treating PSD.